Enhancements of the refractory submicron aerosol fraction in the Arctic polar vortex: feature or exception? - Weigel, R.; Volk, C. M.; Kandler, K.; Hösen, E.; Günther, G.; Vogel, B.; Grooß, J.-U.; Khaykin, S.; Belyaev, G. V.; Borrmann, S. (Atmospheric Chemistry and Physics, 2014)
In situ measurements with a four-channel stratospheric condensation particle counter (CPC) were conducted at up to 20 km altitude on board the aircraft M-55 Geophysica from Kiruna, Sweden, in January through March (EUPLEX 2003, RECONCILE 2010) and in December (ESSenCe 2011). During all campaigns air masses from the upper stratosphere and mesosphere were subsiding inside the Arctic winter vortex, thus initializing a transport of refractory aerosol into the lower stratosphere (Θ < 500 K). The strength and extent of this downward transport varied between the years depending on the dynamical evolution of the vortex. Inside the vortex and at potential temperatures Θ ≥ 450 K around 11 submicron particles per cm3 were generally detected. Up to 8 of these 11 particles per cm3 were found to contain thermo-stable (at 250 °C) residuals with diameters of 10 nm to about 1 μm. Particle mixing ratios (150 mg−1) and fractions of non-volatile particles (75% of totally detected particles) exhibited highest values in air masses having the lowest content of nitrous oxide (70 nmol mol−1 of N2O). This indicates that refractory aerosol originates from the upper stratosphere or the mesosphere. Derived from the mixing ratio of the simultaneously measured long-lived tracer N2O, an empirical index serves to differentiate probed air masses according to their origin: inside the vortex, the vortex edge region, or outside the vortex. Previously observed high fractions of refractory submicron aerosol in the 2003 Arctic vortex were ascribed to unusually strong subsidence during that winter. However, measurements under perturbed vortex conditions in 2010 and during early winter in December 2011 revealed similarly high values. Thus, the abundance of refractory aerosol in the lower stratosphere within the Arctic vortices appears to be a regular feature rather than the exception. During December, the import from aloft into the lower stratosphere appears to be developing; thereafter the abundance of refractory aerosol inside the vortex reaches its highest levels in March. The correlations of refractory aerosol with N2O suggest that, apart from mean subsidence, diabatic dispersion inside the vortex significantly contributes to the transport of particles to the Arctic lower stratosphere. A measurement-based estimate of the total mass of refractory aerosol inside the vortex is provided for each campaign. Based on the derived increase of particle mass in the lower stratospheric vortex (100–67 hPa pressure altitude) by a factor of 4.5 between early and late winter, we estimate the total mass of mesospheric particles deposited over the winter 2009/2010 in the entire Arctic vortex to range between 77 × 103 and 375 × 106 kg. This estimate is compared with the expected atmospheric influx of meteoritic material (110 ± 55 × 103 kg per day). Such estimates at present still hold considerable uncertainties, which are discussed in this article. Nevertheless, the results enable placing constraints on the shape of the so far unknown size distribution of refractory aerosol within the vortex.